Probing ADP Induced Aggregation Kinetics During Platelet-Nanoparticle Interactions: Functional Dynamics Analysis to Rationalize Safety and Benefits - Bandyopadhyay, Souvik K.; Azharuddin, Mohammad; Dasgupta, Anjan K.; Ganguli, Bhaswati; SenRoy, Sugata; Patra, Hirak K.; Deb, Suryyani (Frontiers in Bioengineering and Biotechnology, 2019)
Platelets, one of the most sensitive blood cells, can be activated by a range of external and internal stimuli including physical, chemical, physiological, and/or non-physiological agents. Platelets need to respond promptly during injury to maintain blood haemostasis. The time profile of platelet aggregation is very complex, especially in the presence of the agonist adenosine 5’-diphosphate (ADP), and difficult to probe such complexity using traditional linear dose response models. In the present study, we explored functional data to characterise the pattern of platelet aggregation over time in response to nanoparticle induced perturbations. This has obviated the need to represent the pattern of aggregation by a single summary measure and allowed us to treat the entire aggregation profile over time as the response. The modelling has been performed in a flexible manner, without any imposition of shape restrictions on the curve, allowing smooth platelet aggregation over time. The use of a probabilistic framework not only allowed statistical prediction and inference of the aggregation signatures, but also provided a novel method for the estimation of higher order derivatives of the curve, thereby allowing plausible estimation of the extent and rate of platelet aggregation kinetics over time. In the present study, we focused on the estimated first derivative of the curve obtained from the platelet optical aggregometric profile over time, and used it to discern the underlying kinetics as well as to study the effects of ADP dosage and perturbation with gold nanoparticles. In addition, our method allowed the quantification of the extent of inter-individual signature variations.